Dam Gate Automation Control System by Using Arduino - Hamidun, Muhammad Alif Haiqal; Ibrahim, Siti Aida (Progress in Engineering Application and Technology, 2022)
Every aspect of our lives is connected with the control systems in some way. Control systems are the result of collaboration between hardware and software designers. Even in this day and age of advanced technology, some dams still perform dam gate control procedures manually. There will be human faults and weaknesses if it is done manually. This project describes the creation of a control system for “Dam Gate Automation Control System Based on Arduino”. The objectives are to propose a control system for gate opening based on water level, design a control system of dam gate that can work fully automated by using Arduino and fabricate a prototype of the dam gate control system. With implementation of water level sensor, the opening and closing of the dam gate can be controlled by sending signal to servo motor to control the dam gate’s movement. At various levels, the water level is monitored, and the gate is controlled to close or open.